2007
DOI: 10.1108/00035590710748650
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion of hot end automotive exhaust components

Abstract: Purpose -To evaluate the corrosion resistance of four different stainless steels often employed in hot end exhaust components. Design/methodology/approach -This paper evaluated the outcomes of the hot salt test and the cyclic oxidation test on four different stainless steels, used as hot end exhaust components. The specimens were analyzed by means of SEM for surface changes and the weight loss was considered. Findings -The general corrosion rate and pitting resistance under all the test conditions for hot end … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The complex working environment in automotive exhaust systems has strict requirements for the performance of materials. At the hot end, the working temperatures of exhaust system parts such as exhaust manifold, front pipe, and catalytic converter are usually higher than 600 °C, and thus good heat resistance is required for the materials . Additionally, at the cold end of the exhaust system, the corrosive condensate of exhaust gas could cause the occurrence of pitting perforation in muffler .…”
Section: Introductionmentioning
confidence: 99%
“…The complex working environment in automotive exhaust systems has strict requirements for the performance of materials. At the hot end, the working temperatures of exhaust system parts such as exhaust manifold, front pipe, and catalytic converter are usually higher than 600 °C, and thus good heat resistance is required for the materials . Additionally, at the cold end of the exhaust system, the corrosive condensate of exhaust gas could cause the occurrence of pitting perforation in muffler .…”
Section: Introductionmentioning
confidence: 99%
“…These last ones are also called "superferritic" due to the high stability of ferrite at all temperature. Miyasaki et al (2003) and later Potgieter et al (2007) observed that addition of molybdenum improved drastically resistance to cyclic oxidation as well as high temperature strength of the steel.…”
Section: Introductionmentioning
confidence: 99%
“…The AISI 444 is also stabilised by titanium but additionally alloyed with molybdenum by about 2 wt.%. It was reported that the molybdenum addition could help increase the pitting corrosion resistance [41], the stress corrosion resistance [42], the cyclic oxidation and high temperature strength of the steel [43][44][45]. However, as will be shown in Section 6.6, the molybdenum addition could form Fe-Mo intermetallic compound, which deteriorates the scale adhesion at high temperatures [36].…”
Section: Selection Of Materials For the Use As An Interconnectmentioning
confidence: 99%